NAECON 2018 - IEEE National Aerospace and Electronics Conference 2018
DOI: 10.1109/naecon.2018.8556672
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Networks for Aerial Vehicle Detection and Recognition

Abstract: This paper investigates the problem of aerial vehicle recognition using a text-guided deep convolutional neural network classifier. The network receives an aerial image and a desired class, and makes a yes or no output by matching the image and the textual description of the desired class. We train and test our model on a synthetic aerial dataset and our desired classes consist of the combination of the class types and colors of the vehicles. This strategy helps when considering more classes in testing than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A modified faster R-CNN was applied in the work of Terrail and Jurie [28] that showed promising performances in aerial vehicle detection. In [29], Soleimani et al proposed a text-guided detection scheme using both visual and textual features for detection. Yang et al [30] applied skip connection in their framework to merge lower and higher level features and utilized a focal loss function for vehicle detection.…”
Section: B Deep Learning Based Vehicle Detection Architecturesmentioning
confidence: 99%
“…A modified faster R-CNN was applied in the work of Terrail and Jurie [28] that showed promising performances in aerial vehicle detection. In [29], Soleimani et al proposed a text-guided detection scheme using both visual and textual features for detection. Yang et al [30] applied skip connection in their framework to merge lower and higher level features and utilized a focal loss function for vehicle detection.…”
Section: B Deep Learning Based Vehicle Detection Architecturesmentioning
confidence: 99%
“…A modified faster R-CNN was applied in the work of Terrail et al [28] that showed promising performances in aerial vehicle detection. In [29], Soleimani et al proposed a text-guided detection scheme using both visual and textual features for detection. Yang et al [30] applied skip connection in their framework to merge lower and higher level features and utilized a focal loss function for vehicle detection.…”
Section: B Deep Learning Based Vehicle Detection Architecturesmentioning
confidence: 99%
“…Object detection in satellite imagery remains an ongoing research topic. Soleimani et al [4] investigate the problem of vehicle recognition in aerial imagery using a text-guided deep convolutional neural network classifier. They used a dataset with images captured by drones or Unmanned Aerial Vehicles (UAVs).…”
Section: Related Workmentioning
confidence: 99%